Characterization of the Polarization State of Correlated Stokes–Anti‐Stokes Raman Scattering in Diamond - Freitas, Tiago A.; Machado, Paula; Santo, Marcelo F.; Monken, Carlos H.; Jorio, Ado (physica status solidi (b), 2025)
Quantum information research has been through numerous evolutionary stages, and photonic transport is one of the most promising methods for information processing. Within the context of the use of photons for information transportation, Raman spectroscopy, which consists of an optical spectroscopy technique based on the inelastic scatter of light, where the scattered photons carry information from the vibration structure of the medium, is presented as an exciting way for coding and transportation of quantum information. Herein, the phenomenon of correlated Stokes‐anti‐Stokes (SaS) Raman scattering is explored, analyzing the quantum character of the phenomenon. A state tomography is performed to fully characterize the SaS pair's polarization state. During this study, it is possible to observe the influence of the crystallographic orientation of the diamond on the SaS polarization state, which directly influences the entanglement generation. A Clauser, Horne, Shimony, and Holt‐type Bell's inequality measurement is conducted to confirm the entanglement in the polarization of the SaS state. Transparent condensed matter systems convert two photons from a laser into Stokes and anti‐Stokes time‐correlated photons. Instrumental and data analysis details for time correlation measurements, state polarization tomography, and Bell‐like Clauser, Horne, Shimony, and Holt entanglement tests for Stokes–anti‐Stokes photon pairs generated in diamond are discussed here.